2017
DOI: 10.3847/1538-3881/153/2/63
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of a Distant Massive Planet on the Large Semimajor Axis Trans-Neptunian Objects

Abstract: We explore the distant giant planet hypothesis by integrating the large-semimajor-axis, large-pericenter transNeptunian objects (TNOs) in the presence of the giant planets and an external perturber whose orbit is consistent with the proposed distant, eccentric, and inclined giant planet, so-called planet 9. We find that TNOs with semimajor axes greater than 250 au experience some longitude of perihelion shepherding, but that a generic outcome of such evolutions is that the TNOs evolve to larger pericenter orbi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 58 publications
(111 reference statements)
2
47
0
Order By: Relevance
“…Moreover, the results of Shankman et al (2017) and Lawler et al (2017) pose a problem for the P9 scenario, as already discussed above. It is unclear whether similar issues would also arise in the scenario where EFE, not P9, shapes the orbits of ETNOs.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the results of Shankman et al (2017) and Lawler et al (2017) pose a problem for the P9 scenario, as already discussed above. It is unclear whether similar issues would also arise in the scenario where EFE, not P9, shapes the orbits of ETNOs.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…These two ETNOs have ω and i clustered in line with the original six, but one of them, 2013 FT 28 , has Ω and L with 90 -180 deg offset from the original clustering positions. Shankman et al (2017) demonstrated a drawback of the P9 scenario; they showed that P9 generically drives ETNOs into giant planets crossing orbits, which subsequently decouples them from any shepherding mechanism of P9 and randomises their ω, Ω, and L. Hence, these randomised ETNOs should contaminate the observed sample. However, no such population is observed.…”
Section: Introductionmentioning
confidence: 99%
“…de la Fuente Marcos and de la Fuente Marcos 2014). However, Shankman et al (2017a) have claimed that the Planet Nine hypothesis cannot reproduce the overall level of orbital clustering displayed by the known ETNOs and Shankman et al (2017b) have recently argued that any clustering present among the known ETNOs is probably more apparent than real.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, absence of detection bias is advocated by Trujillo and Sheppard (2014), and by Batygin and Brown (2016), Brown and Batygin (2016) and Brown (2017), while Bannister et al (2017), Lawler et al (2017) and Shankman et al (2017aShankman et al ( , 2017b argue that strong detection biases may actually exist. De la Fuente Marcos and de la Fuente Marcos (2014) showed that there is indeed an intrinsic bias in declination, δ, induced by our observing point on Earth; when observed at perihelion or very near it (see their fig.…”
Section: Introductionmentioning
confidence: 99%
“…This interpretation has been received with scepticism by some members of the scientific community who argue that the currently available data are plagued with strong detection biases Shankman et al 2017;Bannister et al 2017); if observational biases are present, the data are inadequate to prove or disprove the presence of planets beyond Pluto. In stark contrast, a mostly negligible role of detection ⋆ E-mail: nbplanet@ucm.es biases is advocated by Trujillo & Sheppard (2014), and by Batygin & Brown (2016a) and Brown & Batygin (2016).…”
Section: Introductionmentioning
confidence: 99%